La théorie de la transposition didactique: un outil conceptuel pour décrire les savoirs grammaticaux élaborés en classe par les élèves - Isabelle Gauvin (Universitat Autònoma de Barcelona, 2012)
The aim of our research is the description of the grammatical knowledge elaborated by students in the course of verb agreement instruction. This description is achieved through the analysis of the role played by the interactions between the three poles of the didactic triangle (student, teacher and content) in the construction of the content taught.